1991
DOI: 10.1128/jb.173.20.6446-6452.1991
|View full text |Cite
|
Sign up to set email alerts
|

The absence of branched-chain amino acid and growth rate control at the internal ilvEp promoter of the ilvGMEDA operon

Abstract: The question of whether the promoter ilvEp, located in the coding region of ilvM, the second structural gene in the ilvGMEDA operon, is subject to either amino acid-or growth rate-mediated regulation is examined. The experiments described here were performed with ilvEp-cat and ilvEp-lac fusions carried as single copies on the chromosome. The activity of the ilvEp promoter was found to respond neither to the availability of branched-chain amino acids nor to a wide range of growth rates between 35 to 390 min. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…1) encodes five gene products needed for the biosynthesis of leucine, isoleucine, and valine in Escherichia coli K-12 (10,16,27). Three promoters, ilvGp2, ilvEp, and ilvAp, which have been well characterized, initiate transcription just upstream of the ilvG, ilvE, and ilvA genes, respectively (1,15,17,23,28). The presence of two internal promoters, ilvEp and ilvDp, was first inferred by use of strains with polar insertions or mutations located in the ilvGMEDA cluster (4-6), Xilv phage carrying only ilvEDA, ilvDA, or ilvA (13), and fusions to reporter genes (7,17,28).…”
mentioning
confidence: 99%
“…1) encodes five gene products needed for the biosynthesis of leucine, isoleucine, and valine in Escherichia coli K-12 (10,16,27). Three promoters, ilvGp2, ilvEp, and ilvAp, which have been well characterized, initiate transcription just upstream of the ilvG, ilvE, and ilvA genes, respectively (1,15,17,23,28). The presence of two internal promoters, ilvEp and ilvDp, was first inferred by use of strains with polar insertions or mutations located in the ilvGMEDA cluster (4-6), Xilv phage carrying only ilvEDA, ilvDA, or ilvA (13), and fusions to reporter genes (7,17,28).…”
mentioning
confidence: 99%
“…Although it has been demonstrated that this internal promoter is not regulated by the intracellular levels of endproduct amino acids (4,22), it remained possible that it might be growth rate regulated. To examine the in vivo transcriptional activity of ilvp E at different cellular growth rates, a DNA fragment containing this promoter (base pair positions Ϫ223 to ϩ109 relative to the transcription start site of ilvp E [9]) was transcriptionally fused to the lacZ gene and integrated into the genome in single copy (3,23).…”
mentioning
confidence: 99%